2018
DOI: 10.1177/1473325018783823
|View full text |Cite
|
Sign up to set email alerts
|

CARE: The development of an intervention for kinship carers with teenage children

Abstract: The study addresses the needs of Scottish kinship carers of teenage children who have been identified as being in need of extra support. It designs and tests an appropriate support programme, defined as CARE. The CARE intervention study reported here applied the Six Steps for Quality Intervention Development framework, a pragmatic, evidence-based framework. The Six Steps for Quality Intervention Development framework comprises six steps: the first three steps seek to reveal the concerns of the kinship carer gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…However, as discussed in the next stage of this CLR, other models exist, including Wight et al's (2015) 6SQuID, which have been specially developed to promote evidence-based PHI design, planning, and implementation. As documented in the literature, these EBPH-focused change management and PHI design frameworks, especially 6SQuID, have yielded positive outcomes, a prominent example being the Scottish CARE intervention designed by Hartley et al (2018).…”
Section: Theory Of Changementioning
confidence: 99%
See 1 more Smart Citation
“…However, as discussed in the next stage of this CLR, other models exist, including Wight et al's (2015) 6SQuID, which have been specially developed to promote evidence-based PHI design, planning, and implementation. As documented in the literature, these EBPH-focused change management and PHI design frameworks, especially 6SQuID, have yielded positive outcomes, a prominent example being the Scottish CARE intervention designed by Hartley et al (2018).…”
Section: Theory Of Changementioning
confidence: 99%
“…Hence, the justifiable decision was made by the reviewer to include both studies in stage 1 of the present CLR. As documented in the literature, these EBPH-focused change management and PHI design frameworks, especially 6SQuID, have yielded positive outcomes, a prominent example being the Scottish CARE intervention designed by Hartley et al (2018).…”
mentioning
confidence: 99%
“…Despite there being no limitation on the year of publication as an inclusion criterion, all included studies (n = 18) were published between 2013 and 2021 [1,13,14,[18][19][20][21][22][23][24][36][37][38][39][40][41][42][43], and among those, the mode (n = 5) was the year 2021 [19,22,24,39,42]. For more details on the characteristics of each study and the data extracted, see S5 and S6 Appendices.…”
Section: Study Inclusionmentioning
confidence: 99%
“…The studies presented different designs with seven systematic reviews [19,[21][22][23], one scoping review [24], and ten studies with other designs that were considered "methodological" since their primary focus was on how to develop or update a ToC. The included methodological studies had a variety of study methods, as reported by their respective authors: case study (n = 1) [18], mixed methods (qualitative and quantitative) (n = 1) [42], methodology studies (n = 2) [36,37], report (n = 1) [40], formative research (n = 1) [13]. Four publications [1,20,38,43] did not name the study design.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In the U.S. for instance, a kinship carer obtains several resources such as information on changes in family dynamics, financial support, legal support and information on permanent care for a child (Child Welfare Information Gateway, 2022). In Scotland, kinship carers obtain financial aid to cover the needs of the child from the government, with a limitation of 200 euros per week for every child (Hartley et al, 2019).…”
Section: Countriesmentioning
confidence: 99%